Algae Metabolites in Cosmeceutical: An Overview of Current Applications and Challenges - Krishnapriya, T.; Goh, B. H.; Jeon, Y. J.; Yow, Yoon Yen * (MDPI, 2020)
Cosmetics are widely used by people around the world to protect the skin from external stimuli. Consumer preference towards natural cosmetic products has increased as the synthetic cosmetic products caused adverse side effects and resulted in low absorption rate due to the chemicals’ larger molecular size. The cosmetic industry uses the term “cosmeceutical”, referring to a cosmetic product that is claimed to have medicinal or drug-like benefits. Marine algae have gained tremendous attention in cosmeceuticals. They are one of the richest marine resources considered safe and possessed negligible cytotoxicity effects on humans. Marine algae are rich in bioactive substances that have shown to exhibit strong benefits to the skin, particularly in overcoming rashes, pigmentation, aging, and cancer. The current review provides a detailed survey of the literature on cosmeceutical potentials and applications of algae as skin whitening, anti-aging, anticancer, antioxidant, anti-inflammation, and antimicrobial agents. The biological functions of algae and the underlying mechanisms of all these activities are included in this review. In addition, the challenges of using algae in cosmeceutical applications, such as the effectiveness of different extraction methods and processing, quality assurance, and regulations concerning extracts of algae in this sector were also discussed.